An enquiry into Nicolai Hartmann's appreciation of Nietzsche's axiology - Small, Adam (Department of Philosophy, 2016)
In a world and a time when man is confronted with but one ultimate choice: either a return to self-responsibility or the annihilation of life, in which, because of his now proverbial technical ascendancy and its train of spiritual impoverishment, he can indeed neglect to relearn the ability of exercising a wilful choice only at the risk of sacrificing his being as such - in such a world it is a fatal omission to neglect any thinker whose object it is to reconstruct for us our sense of responsibility. In the field of philosophy no contemporary thinker has done more in this respect than Nicolai Hartmann who considers Friedrich Nietzsche to have been his immediate predecessor. Yet Hartmann is not well known in the English-speaking world. The following study represents an attempt to explain Hartmann's position in epistemology, ontology and ethics, stressing the inter-dependence of these disciplines for the philosopher; in the light of Hartmann's appreciation of Nietzsche, to review Nietzsche's critique of "Christo-European morals" or the spiritual decadence of the West; and to show why Hartmann made so much of Nietzsche's supra-moral philosophy of Becoming the philosophy "beyond good and evil".